2017
DOI: 10.18632/oncotarget.23020
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2+ MDSCs promote breast cancer progression by inducing EMT and activated T cell exhaustion

Abstract: Although myeloid-derived suppressor cells (MDSCs) have been demonstrated to contribute to tumor initiation, progression and metastasis, however, which MDSC subsets are preferentially expanded and activated, and what’s the key molecular mechanism responsible for specific MDSC subsets in promoting tumor progression need to be fully addressed. Here we identify that Ly6GmiLy6CloCD11b+CXCR2+ subpopulation (named CXCR2+ MDSCs) are predominately expanded and recruited in systemic and local tumor microenvironment duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…Interestingly, we also indicated that OSCC associated MDSCs accelerated malignant progression of OSCC by enhancing EMT essential for epithelial tumor metastasis. In accordance with our results, researches have demonstrated that CXCR2 + MDSCs were predominately expanded and recruited in breast cancer and could boost EMT of breast cancer cells dependently on IL-6/STAT3 signaling [40]. And the elimination of MDSCs diminished tumor metastasis in breast carcinoma model [41].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we also indicated that OSCC associated MDSCs accelerated malignant progression of OSCC by enhancing EMT essential for epithelial tumor metastasis. In accordance with our results, researches have demonstrated that CXCR2 + MDSCs were predominately expanded and recruited in breast cancer and could boost EMT of breast cancer cells dependently on IL-6/STAT3 signaling [40]. And the elimination of MDSCs diminished tumor metastasis in breast carcinoma model [41].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the absence of PTEN may reduce the infiltration of CD8 + T cells by upregulating VEGF, leading to resistance to PD-1 therapy [94]. MDSCs are negatively correlated with CD4 + and CD8 + T cell infiltration and are an important factor in decreased T cell infiltration [113]. Additionally, the presence of immunosuppressive tumor stroma, especially in some solid tumors, makes it difficult for T cells to infiltrate, limiting the efficacy of PD-1 blockade immunotherapy.…”
Section: Decrease In T Cell Infiltrationmentioning
confidence: 99%
“…It has been shown that MDSCs have a close relationship with PD-L1/PD-1 axis and BCG immunotherapy. 23 , 24 It has been demonstrated that MDSCs could upregulate PD-1 expression in CD8 + T cells and induce activated T cell exhaustion, 23 and in addition, recent studies indicated that CD8 + T cell-to-MDSC balance was associated with the recurrence of BCa undergoing BCG immunotherapy. 24 Patients with a low CD8 + T cell/MDSC ratio showed high recurrence rate after intravesical BCG immunotherapy.…”
Section: Discussionmentioning
confidence: 99%